Characteristics of proximal early gastric cancer differentiating distal early gastric cancer - Koh, Jin Sung (PLoS One, 2019)
Previous studies reported substantial differences between proximal and distal gastric cancer, however, most of the cases included in these studies were advanced gastric cancers (AGCs). The aim of this study was to investigate the unique characteristics of proximal early gastric cancer (EGC) by comparing with distal EGC. From March 2007 to March 2016, proximal and distal EGC patients who underwent endoscopic or surgical resection at our institution were matched 1:3 according to age and sex. We retrospectively analyzed the clinical and histopathological information. A total of 368 patients were enrolled including 92 (25%) in the proximal and 276 (75%) in the distal group. The proportion of patients who underwent surgery (56.5 vs. 20.3%, p<0.001), undifferentiated type (38.0 vs. 19.6%, p<0.001), tumor size (29.5 ±19.4 vs. 20.3 ±16.8 mm, p<0.001) and submucosal (SM) invasion (60.9 vs. 25.7%, p<0.001) were significantly higher in the proximal group than in the distal group. In multivariate analysis, the proximal location of EGC was a significant risk factor for SM invasion in the total population (odds ratio [OR], 3.541; 95% confidence interval [CI], 2.053–6.110; p<0.001), and in subgroup with EGC < 30mm (n = 279) (OR, 5.940; 95% CI, 2.974–11.862; p<0.001). In conclusion, careful therapeutic decision of proximal EGC is essential due to the different histopathological characteristics such as large tumor size and higher potential for SM invasion.